The association between high-activity COMT allele and alcoholism - Serý, Omar; Didden, William; Mikes, Vladimír; Pitelová, Renáta; Znojil, Vladimír; Zvolský, Petr (Neuro endocrinology letters, 2006)
OBJECTIVES: The catechol-O-methyltransferase (COMT) is an enzyme involved in the metabolism of dopamine, adrenaline and noradrenaline. The Val158Met polymorphism of the COMT gene has been previously associated with a variability of the COMT activity, and alcoholism. The aim of the present association study was to examine the relationship between the Val158Met polymorphism of the COMT gene and dispositions to alcoholism. METHODS: In our case control study we analyzed DNA samples from 799 subjects in total (279 male alcoholics and 120 female alcoholics, 151 male controls and 249 female controls). The restriction analysis for the detection of the Val158Met polymorphism was used. RESULTS: We found a relationship between the Val158Met polymorphism of the COMT gene and alcoholism in male subjects. We found the significant difference between male alcoholics and male controls in allele and genotype frequencies (p<0,007; and p<0,04 respectively). CONCLUSIONS: Our study confirmed the relationship between the COMT polymorphism and alcoholism in the Czech male population.
Keywords: alely; Amino Acid Substitution; Alcoholism; Humans; Polymorphism, Restriction Fragment Length; lidé středního věku; polymorfismus genetický; Japonsko; Female; mutace; dospělí; frekvence genu; Alleles; lidé; Japan; Polymorphism, Genetic; DNA; Adult; ženské pohlaví; Male; substituce aminokyselin; Middle Aged; Sex Characteristics; alkoholismus; Gene Frequency; pohlavní dimorfismus; Catechol O-Methyltransferase; polymorfismus délky restrikčních fragmentů; Mutation; mužské pohlaví; katechol-O-methyltransferasa